2020
DOI: 10.3390/jcm9051581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diagnostic Value of MRI and Whole Body 18F-FDG PET/CT in Diagnosis of Spondylodiscitis

Abstract: Spondylodiscitis is a spine infection for which a diagnosis by a magnetic resonance imaging (MRI) is considered the most appropriate imaging technique. The aim of this study was to compare the role of an 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and an MRI in this field. For 56 patients with suspected spondylodiscitis for whom MRI and 18F-FDG PET/CT were performed, we retrospectively analyzed the results. Cohen’s κ was applied to evaluate the agreement between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…10 11 12 13 It could be considered as a complementary or alternative tool to the imaging gold standard MRI for spondylodiscitis. 14 In our case, the intervertebral disc was spared, which is a characteristic feature to differentiate TB from bacterial cause in early vertebral osteomyelitis. Patients with thoracic spine disease are at risk of paraparesis or paraplegia and the disease has to be identified at the earliest.…”
Section: Discussionmentioning
confidence: 51%
“…10 11 12 13 It could be considered as a complementary or alternative tool to the imaging gold standard MRI for spondylodiscitis. 14 In our case, the intervertebral disc was spared, which is a characteristic feature to differentiate TB from bacterial cause in early vertebral osteomyelitis. Patients with thoracic spine disease are at risk of paraparesis or paraplegia and the disease has to be identified at the earliest.…”
Section: Discussionmentioning
confidence: 51%
“…Quantitative analysis : SUV max is the most validated semi-quantitative parameter. No cut-off has been established to differentiate between positive and negative findings; SUV max > 3 seems to be compatible with SI [ 11 ]. Semi-quantitative analysis is also useful to evaluate the response to therapy; in particular, a follow-up SUV max reduction compared to basal value is considered suggestive of a good response to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Lately, few authors [ 42 , 63 - 66 ], both with retrospective and prospective studies, have examined the diagnostic value of 18 F-fluorodeoxyglucose (FDG-PET/CT and MRI in diagnosing SD and its complications ( i.e., epidural and paraspinal abscesses). They concluded that the two techniques are both necessary in diagnosing vertebral osteomyelitis SD and could be considered complementary or a valid alternative to MRI [ 64 ]. FDG-PET/CT is a robust diagnostic tool to diagnose postoperative hardware related spinal infections [ 65 ], and the advantages of an FDG- PET/CT are the larger field of view (FOV), allowing diagnosis of regional abscesses that can be missed on MRI [ 42 , 67 ] and the visualization of metastatic infection especially in patients with bacteriemia, and the possibility to avoid metal implant artifacts [ 42 ].…”
Section: Fdg Pet/ct Imagingmentioning
confidence: 99%